A cascading solar hybrid system for co-producing electricity and solar syngas with nanofluid spectrum selector. (15th August 2019) - Tang, Sanli; Hong, Hui; Jin, Hongguang; Xuan, Yimin
Highlights: Co-production of electricity and solar fuel is enabled with nanofluid selector. Energy loss down by 60% in solar fuel process and 12% in photovoltaics. Key parameters are optimized for the cascading full-spectrum utilization. The system electricity efficiency is 36.3% with 13% less methanol consumption. Abstract: In this paper, a cascading solar energy utilization system is proposed. A nanofluid spectrum selector, which absorbs ultraviolet and infrared sunlight, is adopted. Through a thermochemical reaction, the absorbed sunlight is stored in solar syngas. The nanofluid also transmits visible sunlight to a concentrator photovoltaic module for electricity generation. The nanofluid absorption, photovoltaics and thermochemical processes are coupled to simulate the cascading system. The results reveal that, compared with the individual solar thermal fuel process, the proposed nanofluid receiver can increase the solar-to-fuel efficiency by 15 percentage points. Furthermore, in comparison with the individual photovoltaics, the integrated concentrator photovoltaic module could receive 700–1100 nm sunlight and enhance efficiency by 5.6 percentage points. In a typical case, the cascading system has a solar-to-electricity efficiency of 36.3%. The sensitivity of several key parameters is examined in the solar-to-electricity efficiency. It can be concluded that an operation temperature of 170–200 °C, a particle diameter less than 40 nm and a 3-cm optical thickness are preferred for the optimal performance of the energy converters. The results may provide a pathway of cascading full-spectrum sunlight for the co-production of solar fuel and electricity.